2017
DOI: 10.1111/jse.12264
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number variation and polyploidy in 19 Kaempferia (Zingiberaceae) taxa from Thailand and one species from Laos

Abstract: Several Kaempferia species, endemic to Thailand, are rare and therefore entitled to conservation status; other species are widely cultivated. We conducted extensive cytogenetic investigation of this genus to elucidate the botanical and taxonomic characterization of these plants. The study included 42 accessions belonging to 15 Kaempferia species and four undescribed taxa from regions throughout Thailand, and one species from Laos. We determined chromosome numbers from root‐tip cells collected from germinating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Different base chromosome numbers of Curcuma have been reported. Based on direct chromosome counting, the base chromosome number of x = 16 was reported by Sharma & Bhattacharya (1959), whereas Sato (1960) suggested that it could be x = 7 and 8. Leong-Škorničková et al (2007) proposed, based on genome size data, that x = 7 should be considered a "primary" base chromosome number in Curcuma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Different base chromosome numbers of Curcuma have been reported. Based on direct chromosome counting, the base chromosome number of x = 16 was reported by Sharma & Bhattacharya (1959), whereas Sato (1960) suggested that it could be x = 7 and 8. Leong-Škorničková et al (2007) proposed, based on genome size data, that x = 7 should be considered a "primary" base chromosome number in Curcuma.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of meiotic metaphase chromosomes from microsporocytes was performed using the aceto-carmine smear technique described in Nopporncharoenkul et al (2017). Samples of at least twenty young flower buds from each accession were collected in the field and from local markets.…”
Section: Meiotic Configuration Studymentioning
confidence: 99%
See 3 more Smart Citations